Identifying Promising Application Areas for Cyber-Physical and Complex Event Processing in Logistics Practice - Cyril Alias (Logistics, 2018)
In the course of the ongoing era of digitization, cyber-physical systems and complex event processing belong to the most discussed technologies nowadays. The huge challenge that digitization is forming to the transportation and logistics sector is largely accepted by the responsible organizations. Despite initial steps being taken towards digitized value-creation, many professionals wonder about how to realize the ideas and stumble with the precise steps to be taken. With the vision of smart logistics in mind and cost-efficient technologies available, they require a systematic methodology to exploit the potentials accompanying digitization. With the help of an effective and targeted workshop procedure, potentially appropriate application areas with promising benefit potentials can be identified effectively. Such a workshop procedure needs to be a stepwise approach in order to carefully consider all the relevant aspects and to allow for organizational acceptance to grow. In three real-world use case examples from different areas of the transportation and logistics industry, promising applications of cyber-physical systems and complex event processing are identified and pertaining event patterns of critical situations developed in order to make realization easier at a later stage. Each use case example exhibits a frequently occurring problem that can be effectively addressed by using the above-mentioned technology.